Analisis Kebutuhan dan Perilaku Pencarian Informasi Pengajar Siswa Tunagrahita: Studi Kasus Sekolah Khusus Yayasan Karya Dharma Wanita 01 - Wulandari, Anggi; Nuryudi, Nuryudi (Librarianship in Muslim Societies, 2025)
This study aims to explore how the information needs and information search behavior of high school teachers at SKh Yayasan Karya Dharma Wanita 01, as well as how solutions are made to overcome the obstacles they experience. The method used is qualitative and based on a case study approach. In determining informants, this study uses a purposive sampling technique with three informants who are teachers. The results of this study indicate that the information needs of high school teachers in SKh YKDW 01 are divided into four parts, including: 1) Needs before the new school year, 2) Needs before teaching, 3) Needs when teaching, 4) Students' skill needs to prepare for entering the workforce. The stages of information-seeking behavior carried out by high school teachers in SKh YKDW 01 tend to be in accordance with the stages of information-seeking behavior theory in three models, namely 1) Ellis Model, 2) Kuhlthau Model, and 3) Wilson Model. The solutions used by high school teachers in SKh YKDW 01 to overcome obstacles in searching for information are using existing and free information sources when having difficulty finding information sources about special education and when finding paid information sources. In addition, teachers ask for help from more expert friends when having difficulty finding information on social media and forgetting passwords.